An Efficient Frequency Offset Estimation Method With a Large Range for Wireless OFDM Systems - Guangliang Ren, Guangliang Ren; Yilin Chang, Yilin Chang; Huining Zhang, Huining Zhang; Hui Zhang, Hui Zhang (IEEE transactions on vehicular technology, 2007)
An efficient frequency offset estimation method is proposed for wireless orthogonal frequency-division multiplexing (OFDM) systems. In the proposed method, the received samples of the training symbol are processed by a novel envelop equalized processing method, and the estimation of the frequency offset in the OFDM systems turns out to be the frequency estimation of a complex tone. A novel frequency estimation method is employed to estimate the frequency offset. The estimation range of the proposed method is as large as the bandwidth of the OFDM signal, and the performance of the proposed method is independent of the structure of the training symbol.